2016
DOI: 10.1021/acsami.5b10110
|View full text |Cite
|
Sign up to set email alerts
|

Dismantlable Thermosetting Adhesives Composed of a Cross-Linkable Poly(olefin sulfone) with a Photobase Generator

Abstract: A novel photodetachable adhesive was prepared using a photodepolymerizable cross-linked poly(olefin sulfone). A mixture of a cross-linkable poly(olefin sulfone), a cross-linking reagent, and a photobase generator functioned as a thermosetting adhesive and exhibited high adhesive strength on quartz plates comparable to that obtained for commercially available epoxy adhesives. The cured resin was stable in the absence of UV light irradiation but completely lost its adhesive strength upon exposure of glued quartz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…The results showed that depolymerizable polymers can act as detachable adhesives. The adhesive strength of a poly(olefin sulfone) composed of a volatile olefin monomer and a second olefin monomer possessing a crosslinkable moiety has been evaluated [28]. This polymer was expected to act as a detachable adhesive, as illustrated in Figure 20.…”
Section: Application Of Photo-depolymerizable Poly (Olefin Sulfone)s mentioning
confidence: 99%
“…The results showed that depolymerizable polymers can act as detachable adhesives. The adhesive strength of a poly(olefin sulfone) composed of a volatile olefin monomer and a second olefin monomer possessing a crosslinkable moiety has been evaluated [28]. This polymer was expected to act as a detachable adhesive, as illustrated in Figure 20.…”
Section: Application Of Photo-depolymerizable Poly (Olefin Sulfone)s mentioning
confidence: 99%
“…(1012) Examples for these types of self-immolating polymers include low-ceiling temperature polyaldehydes, polyglyoxylates, metallo-supramolecular polymers, and poly(olefin sulfone)s (POSs). (1317) POSs exhibit low ceiling temperatures and have been shown to undergo triggered depolymerization when exposed to heat,(18) base,(19,20) or ionizing radiation. (21,22) POSs possess main chain sulfonyl (SO 2 ) groups and can be easily synthesized by low temperature free radical polymerization of olefin monomers in liquefied sulfur dioxide.…”
mentioning
confidence: 99%
“…As a result of their characteristics, POSs have been targeted for the development of photoresists and other degradable materials. (19) The generation of radicals, abstraction of acidic protons, or the removal of an electron from the polymer backbone can lead to polymer chain scission, and therefore one triggering event can cause the whole polymer to decompose.…”
mentioning
confidence: 99%
“…Sasaki et al utilized a photodepolymerizable cross‐linked polyolefin sulfone as photodetachable adhesive . A poly(olefin sulfone) copolymer carrying pendant carboxylic acid groups was mixed with a polycarbodiimide cross‐linker and 4,4′‐[bis[[methyl(2‐nitrobenzyl)oxy]carbonyl]‐trimethylene]di‐piperidine] as a photobase generator, which was included to induce photodepolymerization.…”
Section: Irreversible Switching Of the Adhesive Propertiesmentioning
confidence: 99%